Normal Variance Mixture with Arcsine Law of an Interpolating Walk Between Persistent Random Walk and Quantum Walk - Saori Yoshino; Honoka Shiratori; Tomoki Yamagami; Ryoichi Horisaki; Etsuo Segawa (Entropy)
We propose a model that interpolates between quantum walks and persistent (correlated) random walks using one parameter on the one-dimensional lattice. We show that the limit distribution is described by the normal variance mixture with the arcsine law.